Effect of Preheat Temperature Variation with Cooling Media on Mechanical Properties in Welding SS400 Steel - Oktaviandy, Nadya Rachma; Kardiman, Kardiman; Hanifi, Rizal (Universitas Muhammadiyah Jakarta, 2023)
SS400 material is a type of low-carbon steel with a carbon content of 0.17%. It is recognized as low-carbon steel. SS400 steel is commonly employed in shipbuilding and general construction projects. This study recommends the utilization of SS400 steel in tank manufacturing through the Shielded Metal Arc Welding (SMAW) process. Before the SMAW welding process, specimens undergo a specific treatment involving preheating at temperatures of 100°C, 150°C, and 200°C. Subsequently, after preheating, specimens are welded, followed by immersion in a cooling medium, either well water or SAE 15W-40 oil. The preheating and cooling processes aim to enhance the mechanical properties of the material. Impact testing, tensile testing, and microstructure analysis were conducted to evaluate the effects of these treatments. The research results demonstrate a significant improvement in Impact energy, tensile strength, yield strength, modulus of elasticity, and strain in specimens subjected to preheating and cooling treatment. These findings indicate that the use of preheating and cooling can enhance the mechanical performance of SS400 material, providing positive benefits in construction applications that require increased strength and resilience